2008
DOI: 10.3390/molecules14010122
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytotoxicity of MEX: a Component of Neem Oil Whose Action Is Exerted at the Cell Membrane Level

Abstract: Neem oil is obtained from the seeds of the tree Azadirachta indica. Its chemical composition is very complex, being rich in terpenoids and limonoids, as well as volatile sulphur modified compounds. This work focused on the evaluation of a component of the whole Neem oil obtained by methanolic extraction and defined as MEX. Cytotoxicity was assessed on two different cell populations: a stabilized murine fibroblast line (3T6) and a tumor cell line (HeLa). The data presented here suggest a differential sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…In particular, significant increases in MDA level were observed at 1.5 and 2 μg/larva AZA doses at 24 and 72 h, respectively. A similar study on adult wistar rats also revealed that low concentration of A. indica extract increased MDA concentration in brain tissue (Bamidele et al., ) and intracellular formation of MDA in murine fibroblast line (3T6) increased after treatment with methanolic extraction of A. indica (MEX; Ricci et al., ). The latter authors also suggested that MEX caused apoptosis because of oxidative stress with consequent changes of the structure and functional characteristics of plasma membrane (Ricci et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…In particular, significant increases in MDA level were observed at 1.5 and 2 μg/larva AZA doses at 24 and 72 h, respectively. A similar study on adult wistar rats also revealed that low concentration of A. indica extract increased MDA concentration in brain tissue (Bamidele et al., ) and intracellular formation of MDA in murine fibroblast line (3T6) increased after treatment with methanolic extraction of A. indica (MEX; Ricci et al., ). The latter authors also suggested that MEX caused apoptosis because of oxidative stress with consequent changes of the structure and functional characteristics of plasma membrane (Ricci et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…Extracts of neem suppress the proliferation and growth of tumor cells through disruption of cell cycle progression. For example, neem seed oil inhibits growth of HeLa cervical cancer cells [14], and NLE shows proliferation-inhibitory effects in prostate cancer cells [18,19]. Interestingly, the androgen-dependency status fails to modulate anti-proliferative effects of NLE in prostate cancer cells.…”
Section: Neem Components Inhibit Cancer Cell Proliferationmentioning
confidence: 99%
“…Several studies suggest that anti-proliferative and proapoptotic actions of neem are selective for tumor cells. For example, methanolic extraction (MEX) of neem seed oil free of terpenoid/limonoid shows significantly stronger inhibitory effects on the viability of HeLa cells compared to normal murine fibroblasts [14]. Comparison of the oxidative stress level in the two types of cells demonstrates that MEX mixture specifically induces the intracellular level of malonaldialdehyde (MDA) in HeLa cells but not in murine fibroblasts.…”
Section: Therapeutic Safety and Tumor Selective Properties Of Neementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies showed that the HeLa tumour cell line exhibited higher sensitivity to neem oil methanolic extract than stabilized murine fi broblast line (3T6) (Ricci et al 2008 ). The data strongly suggested that its toxic target was the cell membrane and that the extract contained one or more agents with antiproliferative potential.…”
Section: Anticancer Activity In Vitro Studiesmentioning
confidence: 99%